New records of water mites from standing waters in Thailand, with the description of nine new species (Acari: Hydrachnidia) - Savatenalinton, Sukonthip; Smit, Harry (Zootaxa, 2017)
New data are presented of water mites from all kinds of standing waters in Thailand, e.g. reservoirs, ponds, lakes and rice fields. The following new species are described: Nilotonia palustris n. sp., Unionicola boonsaengi n. sp., U. grandiseta n. sp., Neumania diversa n. sp., Piona oryza n. sp., Africasia rotunda n. sp., Arrenurus acutocoxalis n. sp., A. dilatacaudatus n. sp. and A. thailandicus n. sp. The following synonyms are proposed: Mamersa paddicola Jin & Guo, 1993 as a junior synonym of M. rouxi and Limnesia microplatus Wen & Zhu, 2001 as a junior synonym of L. volzi Piersig, 1906. Twenty-five species are reported new for the fauna of Thailand.